Relationship between Spiritual Intelligence and Marital Satisfaction on Wives - Icha Deviani; Ririn Dewanti Dian Samudra Iriani (Indonesian Journal of Cultural and Community Development, 2022)
This study aims to determine the existence of marital satisfaction problems for wives in the village ofPackaging, Krian sub-district, Sidoarjo district. This research method is correlational quantitative with the subject of the wife who is included in the category of early adulthood totaling 161. Determination of the subject using purposive sampling technique where sampling is done by considering certain characteristics. The variables in this study were spiritual intelligence and marital satisfaction. The data collection in this study used two psychological preparation scales, namely the Likert scale for the variables of spiritual intelligence and marital satisfaction made by the researcher. The hypothesis in this study is that there is a positive relationship between spiritual intelligence and marital satisfaction for wives in Packaging Village. Analysis of the data in this study using statistical test of product moment correlation with the help of SPSS 18 for Windows. The results of this study indicate that there is a positive relationship between spiritual intelligence and marital satisfaction for wives in Packaging Village with a value of r = 0.434 with a significance value of 0.000 (P <0.05). This means that there is a significant relationship between spiritual intelligence and marital satisfaction for wives in Packaging Village. So, the results of the initial hypothesis that the researcher proposes can be accepted.